Effects of a Universal Childcare Subsidy on Mothers' Time Allocation - Young Wook Lee (KDI Journal of Economic Policy, 2016)
This paper examines the effects of a universal childcare subsidy on childcare decisions and mothers' employment by using Korea's policy reform of 2012, which provided a full childcare subsidy to all children aged 0 to 2. I find that the introduction of a universal childcare subsidy increased the use of childcare centers by children aged 0-2, which led to less maternal care compared to that provided to children aged 3-4. However, the expanded subsidy had little effect on mothers' labor supply. Moreover, the policy effects vary by individual and household characteristics. The effects of the expanded subsidy are mainly found in low-income households and less educated mothers. Highly educated mothers and high-income households are likely to focus more on the quality of childcare service. These results imply that a simple reduction in childcare costs would bring only limited effects on mothers' time allocation behavior; thus, more attention should be paid to improving the quality of childcare services.
Keywords: J13; J21; J22; I28; 330; Universal childcare; Childcare subsidy; Quality of care; Mothers' time allocation